Loaches of Homatula (Teleostei: Nemacheilidae) from the upper Salween River in Yunnan, China with description of three new species - Li, Xu; Che, Xing-Jin; Zhou, Wei (Zootaxa, 2019)
Seven loaches of Homatula are distributed in a narrow geographical area between the upper Black River (or Song Da in Vietnam, that is a major tributary of the Red River, including the tributaries Lixian-jiang and Tengtiao-jiang in Yunnan, China) and the upper Salween River drainage (including tributaries of the Nu-jiang and Nanding-he, the latter is a major tributary of the Salween River in Yunnan, China). These seven species are distinguished from other Homatula by the combination of having the body densely-scaled, the lateral line complete, and a short adipose crest along the dorsal midline of the caudal peduncle that does not reach the posterior end of anal-fin base or does not extend beyond the middle of the anal-fin base. Based on a comparison with the described species of the densely-scaled group of Homatula, we can confirm that the specimens collected from the Nu-jiang drainage in western Yunnan are different from known species and are described herein as Homatula anteridorsalis sp. nov., Homatula cryptoclathrata sp. nov., and Homatula nigra sp. nov.